KONSEP TEOLOGI HINDU DALAM GEGURITAN GUNATAMA (Tattwa, Susila, dan Acara) - I Wayan Titra Gunawijaya (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
Literary works are the author's intuition in delivering the message to all communities. Also, the creation of the Kakawin/Hindu literature contains a variety of moral messages. However, it must be done in advance for the study of the moral messages contained therein, as well as Geguritan Gunatama which is a literary work in the form of songs/themes which are usually sung on various occasions.The existence of Gunatama's rash in society should certainly be examined in more detail about the story being raised into a rash. Some moral messages that are delivered are not separated from the basic teachings of Hindu religion, the falsafat of life, the way of ethics or behaviour in daily life in accordance with the prevailing norms, then not apart from the event that is the implementation of yajna ritual that is done by the people of Bali in general. Through Gunatama's Geguriatan, the author wants to convey to the wider community about the guidelines of life in accordance with Hindu teachings.